Republic of Croatia : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Croatia. (IMF Staff Country Reports; Country Report, 2008)
Croatia's economic growth accelerated, but external imbalances continued to increase. Executive Directors commended the strong performance accompanied by commendable prudent policies and continued strengthening of financial supervision. They emphasized the need for continued policy efforts to mitigate imbalances and sustain high growth. They stressed the need to continue fiscal adjustment so as to manage domestic demand, address macroeconomic imbalances, and accelerate structural reforms. Directors welcomed the authorities' intention to continue to reduce general government deficit and also pointed the importance of ensuring the sustainability of the pension system.